2014
DOI: 10.5194/bg-11-217-2014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating terrestrial CO<sub>2</sub> flux diagnoses and uncertainties from a simple land surface model and its residuals

Abstract: Abstract. Global terrestrial atmosphere-ecosystem carbon dioxide fluxes are well constrained by the concentration and isotopic composition of atmospheric carbon dioxide. In contrast, considerable uncertainty persists surrounding regional contributions to the net global flux as well as the impacts of atmospheric and biological processes that drive the net flux. These uncertainties severely limit our ability to make confident predictions of future terrestrial biological carbon fluxes. Here we use a simple light-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 95 publications
1
24
0
Order By: Relevance
“…Non-paved portions of the city were defined as deciduous broadleaf forest. Distributions for four land cover types (corn, soy, grassland/pasture, and forest) were derived from the United States Department of Agriculture National Agriculture Statistics Service (NASS; https://nassgeodata.gmu.edu/CropScape/, Han et al 2014), and the VPRM parameters were optimized for these land cover types (Hilton et al 2014) to produce hourly carbon fluxes at 1-km resolution as the weighted average of carbon fluxes from each type. Note that Tower 14 is outside the domain of the VPRM results and is thus not included in the model-data mismatch analysis.…”
Section: Modelled Tower Co2mentioning
confidence: 99%
“…Non-paved portions of the city were defined as deciduous broadleaf forest. Distributions for four land cover types (corn, soy, grassland/pasture, and forest) were derived from the United States Department of Agriculture National Agriculture Statistics Service (NASS; https://nassgeodata.gmu.edu/CropScape/, Han et al 2014), and the VPRM parameters were optimized for these land cover types (Hilton et al 2014) to produce hourly carbon fluxes at 1-km resolution as the weighted average of carbon fluxes from each type. Note that Tower 14 is outside the domain of the VPRM results and is thus not included in the model-data mismatch analysis.…”
Section: Modelled Tower Co2mentioning
confidence: 99%
“…Smaller sharpness values indicate better prediction precision. Reliability is measured using predictive coverage (e.g., Hoeting et al, 1999), which is the percentage of data contained in the prediction interval. Larger predictive coverage values are preferred.…”
Section: Metrics For Evaluating Predictive Performancementioning
confidence: 99%
“…Table 2 CO2 emissions caused by changes in land use, mainly including deforestation and drying of marshes [8] Years 1960-1969 1970-1979 1980-1989 1990-1999 As it turns out, the natural fluxes of CO 2 are much bigger. Terrestrial systems absorb 123 ±8 Gt C/year, converting it to biomass [10,11] and emit 119 ±1 Gt C/year (Table 3). Table 3 Net CO2 absorption by terrestrial ecosystems [8] Years 1960-1969 1970-1979 1980-1989 1990-1999 The observed increase of CO 2 absorption by terrestrial ecosystems is caused by the fertilising effect of rising atmospheric concentration of CO 2 on plant growth, as well as the fertilising effect of nitrogen compounds, mostly nitrogen oxides emitted from industrial plants.…”
Section: Characteristic Of Co 2 Fluxes In Terrestrial Ecosystemsmentioning
confidence: 99%